Collaboration Based Clinical Learning Model For Ners Professional Education Students At RSUP M.Djamil Padang - Rhona Sandra; Alwen Bentri; Ridwan; Darmansyah; Ramalis (CV. AFDIFAL MAJU BERKAH, 2023)
Clinical learning is an educational process that must be passed by undergraduate nursing students at the nursing professional education level, with a study period of 2 semesters, by applying a collaboration-based clinical learning model, but in reality students experience obstacles in achieving learning objectives, resulting in low learning outcomes in clinic. This research is intended to apply the Collaboration-based Clinical Learning Model to Nursing Education students. This research method uses pre-experimental research conducted in the Surgery Room of M.Djamil Hospital, Padang. The samples in this study were selected purposively. Respondents included 12 students who took the Medical Surgical Nursing course for 8 effective weeks. The research data was collected through participatory observation and distributing questionnaires. Data were analyzed using descriptive analysis and dependent T-test. The results of this study indicate that the learning methods applied include: conferences twice a week, clinical tutorials conducted twice for 8 weeks, teaching actions and bedside observations once a week, client care, resumes, and case seminars conducted once for 8 weeks. Among the methods that scored high were: conference 54.5%, BST 54.5%, tutorial clinic 45.4%, client care 72.7%, and case seminar 45.5%. The results of the T-test showed a significant effect of collaboration-based integrated clinical learning methods on learning methods (p=0.006; correlation 43.2%). Discussion of Collaboration-based clinical learning models for Nursing students to be able to apply learning methods that enable students to achieve maximum learning competence. Therefore, this model needs to be continuously developed to help improve optimal learning according to each competency level.